Marketing Problems Encountered by Rice Peoducers and Their Solutons: A Case Study of Takhar-Afghanistan - Roohullah ALAMYAR; İsmet BOZ (ISPEC Journal of Agricultural Sciences, 2021)
The primary purpose of this study was to reveal the marketing problems that rice farmers were experiencing in Takhar province of Afghanistan and to provide solutions for the issue. The field data of the research were obtained from face-to-face surveys and interviews conducted with 90 rice producers in the province. According to the findings of the research, it cannot be said that enough measures have been taken to date in order to increase the contributions of rice sector to the provincial economy. Rice producers in the province are experiencing various problems in production and marketing. Consumers are often condemned to imported products. Farmers grow many different kinds of rice but three of them (Sorha agriculture, Sela, and Lavangi) are preferred by consumers in terms of both taste and quality, as well as their cooking performance. For this reason, production amount of these varieties in the province is higher than other varieties. In order to increase the contribution of the rice sector to the provincial economy, producers’ access to markets should be facilitated, intermediaries should be reduced, and local products should be encouraged.